Hemoglobina O arabia y hemoblobina Hofu: Reporte de tres familias en el Perú. - HAZAN, Eliza; NAVARRO, Juan; MARQUEZ, María del Carmen; CASTILLO, Jorge (Revista Médica Herediana, 2013)
We report the finding of two abnormal hemoglobins in three Peruvian families: hemaglobin O Arab and Hemoglobin Hofu. In the first case the patient was found to be double heterozygous for hemoglobin O Arab/β thalassaemia and presents a moderate chronic hemolytic anemia. In the second family the propositus had a severe chronic of hemoglobin A/O Arab were asymptomatic. In the third case we report a family with a very mild chronic hemolytic anemia due to the presence of hemoglobyn Hofu. These two abnormal hemoglobin O Arabia was introduced in Peru and described the methodology used in the Laboratory to characterize the abnormal hemoglobins.